Analisis Kualitas Website Dinas XYZ dengan Menggunakan Pendekatan ISO/IEC 9126 Untuk Mendukung Continuous Improvement Layanan Publik - Suluh Hidayat; Heni Candra Kirana; Aji Supriyanto (SENTRI: Jurnal Riset Ilmiah, 2026)
The rapid development of e-government initiatives is driving the need for quality public digital services, particularly websites that serve as the primary gateway for information access and administrative interaction. This study aims to evaluate the software quality of the XYZ Department Website using the ISO/IEC 9126 framework and identify aspects that require improvement to support continuous improvement. The evaluation was conducted on six quality attributes: Functionality, Reliability, Usability, Efficiency, Maintainability, and Portability. The study used a quantitative approach through the distribution of Likert-scale questionnaires to 15 respondents, accompanied by direct observation of the system and review of technical documentation. The results showed that all attributes received a "Very Good" classification with a total score of 1184 out of 1500. Usability and Portability were the attributes with the highest scores, indicating that the website has excellent levels of ease of use and cross-device compatibility. Meanwhile, Maintainability and Reliability received relatively lower scores, indicating the need for improvements in regular content updates, page structure consistency, and error handling. Overall, this study concludes that the quality of the XYZ Department website is excellent and capable of effectively supporting public service delivery. However, a continuous improvement strategy is still needed to maintain the quality and sustainability of digital services in the future.